Arab Non-believers and Freethinkers on YouTube: Re-Negotiating Intellectual and Social Boundaries - Elsässer, Sebastian (Religions, 2021)
This article uses the increasing visibility of Arab non-believers in the virtual public sphere as an opportunity to re-examine the key issues and dividing lines between believers, sceptics, and non-believers in Arab societies. It analyzes the currently four most popular Arabic-language YouTube channels created by freethinkers, nonbelievers, and atheists and points out commonalities and differences in style, content, and message. The article argues that the sense of a lively and growing virtual community has raised the confidence of non-believers (lā-dīnīyūn) and atheists in the Arab world and made them more daring in their self-portrayal and in their demands on society. As the examples show, YouTube allows them to circumvent the hostility they face in society and in the mainstream media and to connect with an audience that numbers in the tens of thousands of people from all over the Arab world and the diaspora. The article argues that freethinking and non-belief imply an attempt to re-negotiate social and religious boundaries within Arab societies and could—in the long run—have an impact on legal and constitutional questions as well, such as family law and the prerogatives of religious authorities.